Making enterprise information management (EIM) work for business : a guide to understanding information as an asset - Ladley, John (Morgan Kaufmann, 2010)
Organizations of all types struggle with information. Millions of dollars are spent on ERP applications to integrate data and yet this data still isn't accessible or relevant. Emails contain hidden liabilities. Safety manuals endanger workers. Worse, there is data and information being created and handled in every nook and cranny of large organizations, well out of view of formal oversight, but within view of customers and regulators. Thus far, any efforts to wrestle the "data-beast" to the ground have failed, and there exists a profound need for all levels of business management, not just IT, to understand the risks, challenges, and subsequent remediation value of treating information as a real asset. Making Enterprise Information Management (EIM) Work for Business educates executives and middle management in a way that speaks to business issues and solves business problems. The book is divided into two parts, the first of which defines EIM, addresses why it is required, and identifies the business issues surrounding it. The second part acts as a field guide, or "how-to" that explains how EIM can be worked into any organization via various methodologies, techniques, templates, and business case studies. *Organizes information modularly, so you can delve directly into the topics that you need to understand *Based in reality with practical case studies and a focus on getting the job done, even when confronted with tight budgets, resistant stakeholders, and security and compliance issues. *Includes applicatory templates, examples, and advice for executing every step of an EIM program.